Long noncoding RNA GAS5 accelerates diabetic wound healing and promotes lymphangiogenesis via miR-217/Prox1 axis. (15th July 2021) - He, Zhi-You; Huang, Mi-Tao; Cui, Xu; Zhou, Si-Tuo; Wu, Ying; Zhang, Pi-Hong; Zhou, Jie
Abstract: Background: Diabetes is usually the leading cause of chronic non-healing wounds. LncRNA-GAS5 has been verified to be involved in the regulation of diabetes or high glucose (HG)-stimulated cells. However, its regulatory roles in diabetic wound healing need further investigation. Method: GAS5, miR-217 and Prox1 were identified by qRT-PCR. MTT, flow cytometry assay, wound-healing assay and tube formation were used to analyze cell viability, apoptosis, migration and tube formation capacity. Western blotting was carried out to detect the protein expression of c-Myc, CyclinD1, CDK4, Bcl-2, Prox1, VEGFR-3 and LYVE-1. Bioinformatics and luciferase assay were performed to predict and validate the binding sites of miR-217 on GAS5 and Prox1. Immunofluorescence staining detected the expression and distribution of Prox1. The wound healing rate was also assessed by setting up the diabetic mouse model. H&E staining assessed the distribution of inflammatory cells and fibroblasts in the wound tissues. Results: GAS5 was significantly down-regulated whereas miR-217 was obviously up-regulated in diabetic skin, HG-induced lymphatic endothelial cells (LECs) and diabetic mouse model. GAS5 sponged miR-217 to up-regulate Prox1. GAS5 overexpression or miR-217 inhibition rescued the impairments of cell viability, migration and lymphatic vessel formation and the facilitation of apoptosis of LECs caused by HG. Similar impacts were observed on the protein level of VEGFR-3, LYVE-1, and Prox1. GAS5 promoted wound healing and lymphangiogenesis in the diabetic mouse model. Conclusion: GAS5 sponged miR-217 to up-regulate Prox1 and promote lymphangiogenesis and diabetic wound healing. This might provide novel therapeutic strategy to improve the efficacy of diabetic wound healing. Highlights: GAS5 was down-regulated and miR-217 was up-regulated in diabetic skin wound tissues. GAS5 sponged miR-217 to up-regulate Prox1 expression. GAS5 reduced the effect of HG on LECs activity and lymphangiogenesis by miR-217. GAS5 accelerated wound healing in diabetic mice by promoting lymphangiogenesis.